(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the effect of Quick Ratio (QR), Fixed Asset Turnover (FATO), and Earning Per Share (EPS) on Price to Book Value (PBV) at PT Indocement Tunggal Prakarsa Tbk. The research employed a quantitative associative approach using secondary data obtained from the company’s financial statements for the period 2015–2024. Data were analyzed using multiple linear regression with the assistance of SPSS software, preceded by classical assumption tests, including normality, multicollinearity, heteroscedasticity, and autocorrelation tests. The results indicate that Quick Ratio (QR) does not have a significant effect on PBV, and Earning Per Share (EPS) also does not significantly affect PBV. In contrast, Fixed Asset Turnover (FATO) has a positive and significant effect on PBV. Simultaneously, QR, FATO, and EPS significantly affect PBV, with a coefficient of determination (R²) of 81.4%, indicating that the model has strong explanatory power. These findings suggest that the efficiency of fixed asset utilization plays a crucial role in enhancing firm value as reflected in Price to Book Value